Correlation between grain sizes and electrical properties of CaBi2Nb2O9 piezoelectric ceramics - Chen, Huanbei (2013)
Calcium bismuth niobate (CaBi2Nb2O9, CBN) is a high Curie temperature (TC=930°C) ferroelectrics material and a promising candidate for high-temperature piezoelectric applications. This study focuses on the effect of the grain size on the electric properties and thermal stability of CBN ceramics. The CBN ceramics with different grain sizes were prepared by three different sintering methods: normal sintering, two-step sintering, and hot pressing sintering. Result shows that a strong dependence of piezoelectric properties on the grain size. The d33 of two-step sintering samples with 1.4 μm grain size is 13.5 pC/N which is more than double of that the normal sintering sample with only about 6 pC/N. With the grain size increasing, the unit-cell volume of CBN ceramic is expanded and the TC shift to higher temperature for enhanced stability of the orthorhombic structure. The thermal stability of piezoelectric properties is enhanced from room temperature to near Curie temperature when the grain size is larger than that of 4.3 μm. However, the thermal stability is decreased with decreasing of the grain size since internal stresses provide an additional driving force that assists the thermal depolarization.